PENGARUH PERBEDAAN BERAS ORGANIK, BERAS BETET dan BERAS BULOG TERHADAP POPULASI KUTU BERAS (Sytophilus oryzae) DAN MUTU BERAS SELAMA MASA SIMPAN DI KABUPATEN JAYAWIJAYA - Anti Uni Mahanani; Italia Wantik (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTRice processed from paddy is the main food of Indonesian people in general.Jayawijaya regency is a place that is located in Pegunungan Tengah, Papua Province, can only be connected to the other regencies through air transportation. Rice that is supplied to this regency are varied by quality and brands. Because of those rice supplying condition to this region, automatically, those various rice will be put in storage by both seller and consumer. However, keeping those rice will cause the emergence of pest, in this case, rice lice. Therefore, the purpose of this research was to find out the influence of different types of rice: organic rice, betet rice, and bulog rice to the population of rice lice pest (Sitophilus oryzae) and the rice quality by its storage period in Jayawijaya Regency. This research was conducted in Plant Conservation Laboratory of STIPER Petra Baliem Wamena. This research was conducted for six months which was started June to December 2017. The method of this research was experiment method, and the used design pattern was Random Completed Design. The treatment design was one factor which was consisted of threetypes of rice. Each treatment was repeated by three repeats. The treatment was: types of rice factor: B1: organic rice; B2: betet rice; B3: bulog rice. In this research, there were three treatments, and three repeats so there were nine experiment units. Each unit consisted of packed rice in 0.5 kg plastic for 10 plastics. In each experiment unit, three plastic were taken as samples, so there were 27 rice samples in total. According to the result of the research, we can conclude that bulog rice was able to produce more rice lice (Sitophilus oryzae) and had higher damaging percentage, however, had lesser water and glucose level compared to betet and organic rice.